Association between pregnancy exposure to air pollution and birth weight in selected areas of Norway. Issue 1 (December 2016) - Panasevich, Sviatlana; Håberg, Siri; Aamodt, Geir; London, Stephanie; Stigum, Hein; Nystad, Wenche; Nafstad, Per
Abstract Background Exposure to air pollution has adverse effects on cardiopulmonary health of adults. Exposure to air pollution in pregnancy may affect foetal development. However, the evidence of such effect remains inconsistent. We investigated the effects of exposure to air pollution during pregnancy on birth outcomes. Methods This study, based within the Norwegian Mother and Child Cohort Study (MoBa), includes 17, 533 participants living in the two largest cities in Norway: Oslo and Bergen, and their two surrounding counties: Akershus and Hordaland. Air pollution levels at residential addresses were estimated using land use regression models and back-extrapolated to the period of each pregnancy using continuous monitoring station data. Birth outcomes were birth weight, low birth weight, gestational age, and preterm delivery obtained from the Medical Birth Registry of Norway. Information on lifestyle factors was collected from MoBa questionnaires completed by mothers during pregnancy. Linear and logistic regression models were used to analyse the associations between pregnancy NO2 exposure and birth outcomes. Results We found a statistically significant negative association between pregnancy exposure to NO2 and birth weight −43.6 (95%CI −55.8 to −31.5) g per 10 μg/m3 NO2 . However, after adjusting for either area or the combination of parity and maternal weight, no substantive effects of air pollution exposure were evident. Conclusions Exposure to air pollution during pregnancy was associated with decrease in birth weight, but area-related and lifestyle factors attenuated this association. We found no statistically significant associations of air pollution exposure with gestational age, low birth weight or preterm delivery.